The Role Of The Traffic Police In Enforcing Law Number 22 Of 2009 Concerning Traffic And Road Transportation (Study at the Deli Serdang Police) - Noveri Pardede; Rahul Ardian Fikri; Fitria Ramadhani Siregar (Yayasan Multidimensi Kreatif, 2024)
This study examines the role of the Traffic Police in enforcing Law Number 22 of 2009 concerning Traffic and Road Transportation in the jurisdiction of the Deli Serdang Police. The significant growth in vehicle volume in Deli Serdang, which directly borders the city of Medan, has caused complex traffic problems such as congestion, traffic violations, and accidents. This study aims to analyze the role of the Deli Serdang Police Traffic Police in enforcing traffic laws and identify the obstacles faced. Data were obtained through a case study at the Deli Serdang Police using qualitative methods, including interviews with Traffic Police officers and field observations. The results of the study indicate that the Deli Serdang Police Traffic Police have implemented various law enforcement efforts, both preventive and repressive, but face several obstacles such as limited personnel, facilities and infrastructure, and low public awareness in complying with traffic rules. This study recommends increasing the capacity of the Traffic Police, providing adequate facilities and infrastructure, and intensifying socialization and education to the public to increase the effectiveness of traffic law enforcement in Deli Serdang.